(untitled) (Global Journals of Research in Engineering, 2012)
Massive defective products as a result of faulty heat- treatment process of a specific steel alloy, DIN 100CrMn6, are observed as a series issue. This is due to the remarkable market loss faced on the target industry of this research, Akaki Basic Metals Industry. The defective product of the stated steel alloy, mill grinding steel ball of cement industry, was observed and made reproduced its actual prototype using the same material and following the same production flow of the target industry. Three stages of the production flow were selected and the necessary tests, metallographic structure and the chemical composition, of the material were conducted at each selected process stages. The test stages adopted are; testing the raw material, the just as forged, and the heat treated final product. From the chemical composition and metallographic structure result of the first test stage, the mostly pearlite.